Strengthening expertise for health technology assessment and priority-setting in Africa - Jane E Doherty; Thomas Wilkinson; Ijeoma Edoka; Karen Hofman (Taylor & Francis Group, 2017)
Background: Achieving sustainable universal health coverage depends partly on fair priority-setting processes that ensure countries spend scarce resources wisely. While general health economics capacity-strengthening initiatives exist in Africa, less attention has been paid to developing the capacity of individuals, institutions and networks to apply economic evaluation in support of health technology assessment and effective priority-setting. Objective: On the basis of international  lessons, to identify how research organisations and partnerships could contribute to capacity strengthening for health technology assessment and priority-setting in Africa. Methods: A rapid scan was conducted of international formal and grey literature and lessons extracted from the deliberations of two international and regional workshops relating to capacity-building for health technology assessment. 'Capacity' was defined in broad terms, including a conducive political environment, strong public institutional capacity to drive priority-setting, effective networking between experts, strong research organisations and skilled researchers. Results: Effective priority-setting requires more than high quality economic research. Researchers have to engage with an array of stakeholders, network closely other research organisations, build partnerships with different levels of government and train the future generation of researchers and policy-makers. In low- and middle-income countries where there are seldom government units or agencies dedicated to health technology assessment, they also have to support the development of an effective priority-setting process that is sensitive to societal and government needs and priorities. Conclusions: Research organisations have an important role to play in contributing to the development of health technology assessment and priority-setting capacity. In Africa, where there are resource and capacity challenges, effective partnerships between local and international researchers, and with key government stakeholders, can leverage existing skills and knowledge to generate a critical mass of individuals and institutions. These would help to meet the priority-setting needs of African countries and contribute to sustainable universal health coverage.